1969
DOI: 10.1139/v69-509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chain length on storage stability and hydrolytic reversion of sodium polyphosphate glasses

Abstract: At low concentrations in hard water, the polyphosphates revert to orthophosphate at rates which are not predictable from data obtained at higher concentrations. A reversal in the effect of pH on reversion rate at lower concentrations appears to be due to complex formation between the polyphosphate and the hard water metal ions. A minimum in the rate of reversion of polyphosphate glasses to orthophosphate occurs at an average chain length between about 13 and 40 under the low concentration hard water conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2 As pure polyphosphates, these materials are unstable to hydrolysis, 3 breaking down rapidly in basic media to smaller phosphate units, which are soluble in water. This, combined with the presence of phosphates in hydroxyapatite, have lead to several investigations into the practicalities of these materials for bone augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…2 As pure polyphosphates, these materials are unstable to hydrolysis, 3 breaking down rapidly in basic media to smaller phosphate units, which are soluble in water. This, combined with the presence of phosphates in hydroxyapatite, have lead to several investigations into the practicalities of these materials for bone augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate can be a nutrient for microbes; therefore, the presence of biofilm may increase hydrolysis. The effect of pH is less understood; some reports show that lower pH around 7 causes higher reversion rate, , whereas others showed the opposite trend. , …”
Section: Chemistry Of Orthophosphate and Polyphosphatementioning
confidence: 99%
“…15 Breaking a molecule midchain may also occur, although little evidence supports this mechanism. 16 The reversion rate increases at higher chain lengths, 17 higher temperatures, 18,19 longer water age, and lower alkalinities. 15 In addition, the presence of divalent cations and certain pipe materials, 15 biological growth, and pH may also increase reversion rates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Polyphosphate glasses are known to hydrolyze and break down into smaller water-soluble phosphate units. 9 Earlier work has focused on the role of calcium concentration on the degradation of polyphosphate glasses manufactured over the same time period. 10 Effects of prolonged heating during the manufacture of polyphosphate glasses suggest that the addition of calcium phosphate will result in a decrease in the degradation rate of the glass as previous research has found addition of 12 calcium units causes a change in degradation rate from approximately 0.1 g/cm 2 per hour to approximately 0.02 g/cm 2 per 100 h. 10 Osteoblast responses to such glasses have been analyzed demonstrating that the inclusion of calcium, which resulted in a significant decrease in solubility rate (as detailed above), had positive effects on proliferation and antigen expression.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphosphate glasses are known to hydrolyze and break down into smaller water‐soluble phosphate units 9…”
Section: Introductionmentioning
confidence: 99%